Nonlinear effects in fiber lasers and amplifiers: review of pulse generation at 1550–1870 nm wavelength range - Diana Galiakhmetova (Advances in Physics: X)
Fiber lasers, operating in the NIR-III spectral region (1550–1870 nm), have attracted the attention of scientists due to their widespread applications and potential advancement of biomedical tools and clinical laser-based systems. However, developing tunable NIR-III ultrashort pulsed lasers is still challenging due to the lack of efficient rare-earth-doped fibers, reviewed in this paper. Overcoming these challenges and achieving wide tunability are possible by implementing methods based on nonlinear optical effects. This review presents recent advances in developing NIR-III fiber lasers, including the explanation of nonlinear effects such as self-phase modulation, four-wave mixing, stimulated Raman scattering, soliton self-frequency shift, and supercontinuum generation. In addition, the paper discusses the advantages and drawbacks of each method and makes recommendations for future development trends and improvements.